Caracterização genética de populações de Lutjanus jocu (Block & Shneider, 1908) por meio de marcador mitocondrial (mtDNA) - Cheida, Isabela Mayara (2014)
Fish present themselves the most diverse vertebrate and most known by genetic variation. The Perciformes order is characterized by being more diverse and more numerous, which stresses Lutjanus jocu, for being an important economic resource of industrial fishing, from small to medium sized in Brazil . Despite major advances in science, there is acute shortage of information on this species in question, particularly in the case of scientific data and technical support to establish management and conservation programs. In this context, this work aimed to characterize genetically the population structure of Lutjanus jocu using the mitochondrial marker Dloop hypervariable region (control region) at certain points along the Brazilian coast. Altogether, 65 samples had their DNA extracted, amplified and sequenced, generating a 420 bp consensus tape. The Fst index Wright presented was low and positive, ranging between 0.023 and 0.076 (p = 0.95). The analysis of molecular variance corroborate the values fobuyn d the Fst index, which showed low value, but positive (V = 1.387). These values indicthataet there was a slight genetic differentiation between populations, evidenced by phylogenetic trees. The values fofuonrd tests of neutrality of Tajima (Tajima 1989) and Fu (Fu, 1997) were negative for both tests (D = 0.9059 and Fs = 2901, P> 0.05 respectively) suggesting expansion population. Genetic studies using nuclear markers are needed to better understand the species and to identify donor arrays of genes, as an alternative to the preservation and maintenance of L.jocu stocks.